f ( θ ) = sin ( θ ) sin ( 5 θ ) sin 2 ( 4 θ ) − sin 2 ( θ )
Let function f ( θ ) be defined as above. Find n = 0 ∏ 8 ( f ( 2 n − 1 θ ) − 1 ) , where θ = 5 1 3 π .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simplifying the given function,
f ( θ ) = sin ( θ ) sin ( 5 θ ) sin ( 4 θ + θ ) sin ( 4 θ − θ ) .......................................................................................................( sin 2 ( A ) − sin 2 ( B ) = sin ( A + B ) sin ( A − B ) )
f ( θ ) = sin ( θ ) sin ( 5 θ ) sin ( 5 θ ) sin ( 3 θ )
f ( θ ) = sin ( θ ) sin ( 3 θ )
f ( θ ) = sin ( θ ) 3 sin ( θ ) − 4 sin 3 ( θ ) ..........................................................................................................(Triple angle formula)
f ( θ ) = 3 − 4 sin 2 ( θ )
f ( θ ) = 1 + 2 ( 1 − 2 sin 2 ( θ ) )
f ( θ ) = 1 + 2 cos ( 2 θ ) ............................................................................................................(Double angle formula)
Thus,
f ( θ ) − 1 = 2 cos ( 2 θ )
And hence,
f ( 2 n − 1 ( θ ) ) − 1 = 2 cos ( 2 × 2 n − 1 ( θ ) )
That is,
f ( 2 n − 1 ( θ ) ) − 1 = 2 cos ( 2 n ( θ ) )
Now,
∏ n = 0 8 ( f ( 2 n − 1 ( θ ) ) − 1 ) = 2 cos ( θ ) × 2 cos ( 2 θ ) × . . . . . . . . . × 2 cos ( 2 8 θ )
∏ n = 0 8 ( f ( 2 n − 1 ( θ ) ) − 1 ) = 2 9 ( cos ( θ ) × cos ( 2 θ ) × . . . . . . . . . × cos ( 2 8 θ ) )
∏ n = 0 8 ( f ( 2 n − 1 ( θ ) ) − 1 ) = 2 9 ( 2 9 sin ( θ ) sin ( 2 9 θ ) ) ..............................................................................( ∏ r = 0 n − 1 cos ( 2 r θ ) = 2 n sin ( θ ) sin ( 2 n θ ) )
∏ n = 0 8 ( f ( 2 n − 1 ( θ ) ) − 1 ) = sin ( θ ) sin ( 2 9 θ )
Putting θ = 5 1 3 π ,
Answer = sin ( 5 1 3 π ) sin ( 5 1 3 5 1 2 π )
Answer = sin ( 5 1 3 π ) sin ( π − 5 1 3 π )
Answer = sin ( 5 1 3 π ) sin ( 5 1 3 π ) ....................................................................................................................( sin ( π − θ ) = sin ( θ ) )
Answer = 1
Problem Loading...
Note Loading...
Set Loading...
Similar solution as @Saurav Dosi 's, different presentation.
f ( θ ) = sin θ sin 5 θ sin 2 4 θ − sin 2 θ = sin θ sin 5 θ sin 5 θ sin 3 θ = sin θ sin 3 θ = sin θ 3 sin θ − 4 sin 3 θ = 3 − 4 sin 2 θ = 1 + 2 ( 1 − 2 sin 2 θ ) = 1 + 2 cos 2 θ As sin 2 A − sin 2 B = sin ( A + B ) sin ( A − B ) As sin 3 θ = 3 sin θ − 4 sin 3 θ As cos 2 θ = 1 − 2 sin 2 θ
Therefore,
P = n = 0 ∏ 8 ( f ( 2 n − 1 θ ) − 1 ) = n = 0 ∏ 8 ( 1 + 2 cos ( 2 ⋅ 2 n − 1 θ ) − 1 ) = n = 0 ∏ 8 ( 1 + 2 cos 2 n θ − 1 ) = n = 0 ∏ 8 2 cos 2 n θ = 2 9 cos θ cos 2 θ cos 3 θ . . . cos 8 θ = sin θ 2 9 sin θ cos θ cos 2 θ cos 4 θ . . . cos 2 5 6 θ = sin θ 2 8 sin 2 θ cos 2 θ cos 4 θ cos 8 θ . . . cos 2 5 6 θ = sin θ 2 7 sin 4 θ cos 4 θ cos 8 θ cos 1 6 θ . . . cos 2 5 6 θ = . . . = sin θ sin 5 1 2 θ Putting θ = 5 1 3 π = sin 5 1 3 π sin 5 1 3 5 1 2 π As sin ( π − x ) = sin x = sin 5 1 3 π sin 5 1 3 π = 1